Construção do conhecimento: um estudo da educação Kokama na comunidade Nova Esperança - Souza, Alcione Deodato de (2021)
This study addresses Indigenous School Education (IES) at the Municipal Center for Indigenous School Education Atawanã Kuarachi Kokama. With the title, The Construction of Recognition: a study of Kokama education in the Nova Esperança community, we seek to highlight the community's leading role in its own processes of constituting an Indigenous School Education according to the reality and perspectives of the community. During the research, we reflected on the process of building the school (a process that is still ongoing). Our general objective is to analyze the paths taken and the difficulties faced by the Kokama community to carry out a proposal for a differentiated and intercultural Indigenous School Education. As specific objectives, we propose to write the institutional processes for the implementation of Indigenous School Education in SEMED; analyze the process of creation and implementation of the CMEEI in the Kokama community; and, identify the strategies used by the Kokama and CMEEI, during the period of the Covid-19 pandemic, to carry out school activities. The approach used was through digital ethnography, with bibliographic and documentary data, based on Flick (2009), Gil (2002) and Godoy (1995). The results show that at CMEEI there is work based on the principles of differentiated, intercultural and bilingual education, in which traditional knowledge and knowledge and the Kokama language are part of the pedagogical proposal of the school.